Die geheim van die prediking: om na die stem van die teks te luister - Cilliers, Johan (Verbum et ecclesia, 2002)
The secret of preaching: listening to the voice of the Biblical text This paper concentrates on the function of the Biblical text in preaching, contending that there can in fact be no preaching in the true sense of the word if the text is not honoured both in its content and form. It argues that a significant percentage of contemporary preaching has lost its Biblical integrity because (a) it does not understand the basic need for and character of meditation, (b) it has lost the art of reading the text, (c) it does not utilize the text as source of creative structuring, and (d) it fails to understand the very nature of the text as Biblical text. Albeit an introduction, it tries to combine the contributions of the communication and literary sciences with classical homiletical approaches, for example those of Augustine and Luther, in answering the question: when can preaching be called Scriptural?